2015
DOI: 10.1127/metz/2014/0600
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking in a rotating annulus: a comparative experimental and numerical study of baroclinic wave dynamics

Abstract: The differentially heated rotating annulus is a widely studied tabletop-size laboratory model of the general mid-latitude atmospheric circulation. The two most relevant factors of cyclogenesis, namely rotation and meridional temperature gradient are quite well captured in this simple arrangement. The radial temperature difference in the cylindrical tank and its rotation rate can be set so that the isothermal surfaces in the bulk tilt, leading to the formation of baroclinic waves. The signatures of these waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Hence, this system is well suited to study the dynamics observed in atmospheric baroclinic waves at midlatitudes. Various studies were conducted to investigate baroclinic-wave life cycles and the corresponding jet-front system in the rotating annulus (Früh & Read 1997;Sitte & Egbers 2000;von Larcher & Egbers 2005;Harlander et al 2012;Vincze et al 2014). More recently, the annulus has also been used to examine the generation and propagation of IGWs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this system is well suited to study the dynamics observed in atmospheric baroclinic waves at midlatitudes. Various studies were conducted to investigate baroclinic-wave life cycles and the corresponding jet-front system in the rotating annulus (Früh & Read 1997;Sitte & Egbers 2000;von Larcher & Egbers 2005;Harlander et al 2012;Vincze et al 2014). More recently, the annulus has also been used to examine the generation and propagation of IGWs.…”
Section: Introductionmentioning
confidence: 99%
“…It has also proved valuable as a tractable 'test bed' within which to test numerical codes and methods (Harlander et al 2011;Vincze et al 2015) as well as to benchmark statistical-dynamical analysis methods in widespread use in meteorology, such as data assimilation (Young and Read 2013). Moreover, it is even inspiring new experiments for studying non-terrestrial planetary atmosphere dynamics in the laboratory (Read et al 2015;Yadav et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…19. The temperature records were obtained using an ALMEMO temperature sensor array of NiCr sensors with a relative resolution of 0.05 K and 1 Hz sampling rate.…”
Section: Methodsmentioning
confidence: 99%